РOLICY OF INSURANCE PROTECTION AND STRATEGY OF ITS REFORM IN UKRAINE - A. Zaletov (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article deals with the essence of the role and tasks of the insurance policy in modern conditions. Insurance is defined as a system of policy measures authorities and business entities to use the tools of insurance and financial resources of insurers in order to effectively manage risks and ensure the implementation of the goals and objectives of socio-economic development of the country (region) and business entities. Allocated to the insurance policy of the state, the corporate sector, households and insurance (reinsurance) companies. The economic, social and informational categories of state regulation in the insurance industry, underlined the need to reform the insurance market taking into account the influence of external and internal threats. Define the objectives and principles of the strategy of reforming the system of state regulation of the insurance market of Ukraine. Proposed priorities for the development of the insurance market on the basis of deregulation and simplification of the regulatory environment, improvement of activity control and efficiency of state supervision, protecting the interests of insurance consumers and restore confidence in the insurance market.